Green Procurement Practices, Ethical Procurement and Value for Money with Empirical Evidence from Ghana - Yeboah, Samuel Ankomah; Abu Hasan, Zuha Rosufila; Abdul Halim, Muhammad Abi Sofian (International Review of Management and Marketing, 2026)
Achieving UN Sustainable Development Goal 12, has multiplier effects on attainment of other SDGs. In line with this assertion, the current study is aimed to examine the influence of green procurement practices on value for money and the mediating role of ethical procurement in the agricultural sector in Ghana. The study positions green procurement as a multi-dimensional construct proxied as; green purchasing, supplier selection, and supplier development, and places ethical procurement as being the governance tool which turns sustainability activities into performance results. The study is based on positivists’ paradigm, quantitative approach, and a cross-sectional survey design using the participants from procurement and supply chain specialists among agribusiness firms in Ghana. Our hypothesized relationships have been tested by using Structural Equation Modelling (SEM) with the aid of SMART-PLS version 4.1.1. The results showed that all three dimensions of green procurement exert significant positive effects on ethical procurement. Moreover, ethical procurement has a very significant benefit on value for money, which includes improvements in accountability, efficiency, and lifecycle cost optimization. Crucially, ethical procurement plays a mediating role between green procurement practices and value for money, The analysis finds that green procurement does not automatically translate into greater value for money. Theoretically, the study provides a contribution by recasting ethical procurement as an organisational capability and empirically by providing evidence from the context of an emerging economy (Ghana). From a practical perspective, these findings suggests that ethical enforcement mechanisms, supplier governance systems and standards of professional procurement must be enshrined within green procurement practices to optimize benefits and in terms of economic and sustainability aspects to policymakers and managers.